Las compensaciones y su relación con el desempeño laboral de los colaboradores de la empresa Fundo Muchick - Danper S.A.C. - 2017 - Jimenez Rosales, Merlyn Loren (2018)
The present research work was developed in the Fundo Muchick Company - DANPER SAC, which, like any company, seeks to be a leader in its field, and to achieve this, it has been investigated whether the current compensations perceived have a positive impact on the performance of the collaborators, since compensation is considered one of the main factors that influence the motivation of employees, and for the company is a strategic method that can be used to retain the best talent of the company. The non-experimental, cross-sectional and correlational and descriptive type of research, the Inductive-Deductive Method, the Hypothetical-Deductive Method was used, the survey was also used as a research technique, the Cronbach's Alpha method was used to verify the reliability of the data obtained and the Pearson coefficient was used to establish the relationship of the compensations with the labor performance. For the development of the research work, the population that was made up of the collaborators of Empresa Fundo Muchick - DANPER SAC, a representative sample was obtained, using the statistical method, then the data collection instrument was applied, with the information obtained it was possible to meet the objectives of the thesis, check the research hypothesis, and determine that the compensations are related to the work performance in a positive and significant way, where r = 0.82.